PENGEMBANGAN MEDIA PEMBELAJARAN SENI BERBANTUAN FILMORA DI SEKOLAH DASAR - Afriadi, Putra; Ratno, Suyit; Khairina, Mifta (Universitas Negeri Medan, 2024)
Developing effective and interesting learning media is very important in the educational process, especially at the elementary school level. This article discusses the development of art learning media assisted by Filmora video editing software at Cinta Rakyat Elementary School 104208. The research method used is Research and Development (R&D) based on the model proposed by Borg and Gall. Research steps include initial research and information gathering, planning, product draft development, initial field trials, product revisions, main field trials, final product revisions, and dissemination. The research results show that the use of Filmora in art learning is effective in increasing students' interest, understanding and art skills. Students are more enthusiastic and creative in taking art lessons using Filmora-assisted learning media compared to conventional methods. Teachers also find it easy to convey art material in a more interactive and interesting way. This learning media helps students learn more practically and contextually, which in turn increases their understanding of the material being taught. Thus, the development of art learning media assisted by Filmora can be an innovative solution to improve the quality of art learning in elementary schools. It is hoped that this article can be a reference for educators in utilizing technology to create a more enjoyable and meaningful learning experience for students.